Enlightening the "Spirit Molecule": Photomodulation of the 5‐HT2A Receptor by a Light‐Controllable N, N‐Dimethyltryptamine Derivative. Issue 26 (29th April 2022) - Gerwe, Hubert; He, Feng; Pottie, Eline; Stove, Christophe; Decker, Michael
Abstract: Classical psychedelics are a group of hallucinogens which trigger non‐ordinary states of consciousness through activation of the 5‐HT2A receptor (5‐HT2A R) in the brain. However, the exact mechanism of how 5‐HT2A R agonism alters perception remains elusive. When studying receptor signaling, tools which work at the same spatiotemporal resolution as the receptor are exceptionally useful. To create such a tool, we designed a set of photoswitchable ligands based on the classical psychedelic N, N ‐dimethyltryptamine (DMT). By incorporation of the DMT‐indole ring into the photoswitchable system, we obtained red‐shifted ligands which can be operated by visible light. Among these azo‐DMTs, compound 2 h ("Photo‐DMT") stands out as its cis isomer exhibits DMT like activity while the trans isomer acts as weak partial agonist. Such a cis ‐on "efficacy switch" substantially expands the pharmacological toolbox to investigate the complex mechanisms of 5‐HT2A R signaling. Abstract : N, N ‐Dimethyltryptamine (DMT) was made photoswitchable following an "azo‐extension" approach on the indole moiety. A library of azo‐DMTs was synthesized out of which 5‐(4‐MeO)‐azo‐DMT (Photo‐DMT) acted as cis ‐on "efficacy switch".